Food and the pilgrim: nourishment for pilgrims and faith-based tourists - Munro, Dane; Buttigieg, Noel; Olsen, Daniel H. (Pilgrimage studies, 2023)
"Presented in this volume, the first of its kind that is entirely dedicated to food in the context of pilgrimage and faith-based tourism, are different case studies gathered for the benefit of academia, pilgrimage stakeholders, faith-based tourism stakeholders, planning and policy makers, tourist guides, students and interested readers. This knowledge hopefully will find its way into practical applications and educational materials. The potential of this volume is that the contributors have researched food as an addendum of the spiritual experience of food within the context of pilgrimage and faith-based tourism, namely that giving, receiving and sharing promotes respect and understanding. Food can be used simultaneously as an active peace-building tool, to promote inclusion, bridging cultures and harmony at table"--